Non-Standard Vocabulary of Indonesian Language in Students' Reviews Texts of Vocational School Giri Taruna Bogor - Septiani, Dwi (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
One of the things that students lack mastery of, both at the secondary and tertiary levels, is when writing, namely the lack of accuracy in writing standard vocabulary that is in accordance with standard Indonesian spelling. This study aims to describe the writing of non-standard Indonesian vocabulary in a review text by students of SMK Giri Taruna Bogor. The subjects of this study were students of class XI SMK Giri Taruna Bogor FY 2020/2021 totaling 30. The method used in this study was a qualitative descriptive method. Based on the data obtained, there are 30 simple text reviews for class XI students of SMK Giri Taruna Bogor FY 2020/2021. The result of this research is the finding of writing 125 non-standard vocabularies in all of the students' review texts. Only 1 student review text work with data number 04 has 1 standard vocabulary writing error, namely the word analysis which should be written as analysis. On the other hand, the most non-standard vocabulary writing was done by students with data number 15, namely there were 10 writings of non-standard vocabulary.